USM 54th CONVOCATION 24 – 27 OCTOBER 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 September 2016 – Some 5,947 graduands would be receiving their degrees and diplomas at the 54 Universiti Sains Malaysia (USM) Convocation Ceremony, to be held from 24 27 October 2016 (Monday to Thursday), within a duration of 4 days, in 8 sessions at the Dewan Tuanku Syed Putra, USM Penang.